Social cognition and emotional rehabilitation in participants with schizofrenia - Rodríguez Pulido, Francisco; Caballero Estebaranz, Nayra; García Caballero, Alejandro Alberto; González Dávila, Enrique; León Palacín, Celia; Hernández Álvarez de Sotomayor, María del Carmen; López Reig, Susana; Vílchez de León, Patricia Inés (Frontiers in Psychiatry, 2023)
People with schizophrenia have deficits in social cognition, emotion and social perception, as well as attributional style. The purpose of this study was to evaluate the efficacy of a multicomponent social cognition training program, e-Motional Training® (ET), in people with schizophrenia and to compare its efficacy with people who did not receive it. Therefore, a single-blind RCT was conducted in participants with a diagnosis of schizophrenia. A randomized, single-blind, clinical trial was conducted with 50 stable outparticipants with schizophrenia (registry number CHUC_2019_109). All participants (control and intervention) were treated with pharmacotherapy, case management and were on Individual Placement and Support methodology for competitive employment. The intervention group was treated with ET, an online program designed for social cognition rehabilitation. Pre and post assessment was performed using different battery of tests. General mixed models with subject identification and repeated measures over time were used. Different pre and post measurements were performed in the two groups. No significant differences were found in sociodemographic characteristics between the control and intervention groups. Improvements were obtained in the intervention group in the Ekman test (P = 0.009), mainly enhanced by the improvement shown in three emotions: fear, sadness and disgust (P = 0.041, P = 0.021 and P = 0.038 respectively). ET is a promising online training tool for social cognition deficits in schizophrenia, in particular, for the improvement of emotions.